ANALYSIS OF PROBLEMS ARISING IN DEVELOPING STUDENTS' LINGUISTICAL-METHODICAL THINKING (SCIENCE TIME JOURNAL, 2026)
This research examines the problems that arise in the process of developing students’ linguistical-methodical thinking, which plays a crucial role in language learning and teaching. Linguistical-methodical thinking refers to the ability of students to analyze linguistic phenomena and apply methodological principles effectively in language acquisition and instruction. The study identifies key challenges such as insufficient theoretical knowledge, limited practical application, lack of critical and analytical skills, and ineffective teaching methods. The research also analyzes pedagogical approaches and methodological strategies that can enhance students’ ability to think linguistically and methodically. The findings emphasize the importance of integrating theory with practice, using innovative teaching methods, and promoting independent and analytical thinking among students. This study contributes to improving the quality of language education and the professional competence of future language specialists.